KESIAPAN DAN KETERLIBATAN PENDIDIK PAUD DI JAWA TIMUR PADA MASA PANDEMIK COVID-19 MELALUI PENGUASAAN TIK - anggraini, kristin (incrementapedia, 2020)
This research was driven by a change in the implementation of learning in PAUD during the Covid-19 pandemic virus, which was originally conducted face-to-face and turned into virtual. Based on this, the researcher wants to know the readiness, willingness and involvement of PAUD educators in implementing virtual learning. This research is a qualitative research with literature-based data sources collected from several articles contained in various international journals and surveys that have been conducted to about two hundred and fifty-six teachers in East Java who confirmed that as many as 10.5% stated strongly agree, as many as 50.4% agreed while 39.1% stated that they did not agree / were not willing to support efforts to implement virtual learning for early childhood. The results of this study are expected to be a recommendation for policy makers to carry out virtual learning in early childhood classes in order to break the chain of the spread of the Covid-19 virus in Indonesia.